Technical and tactical aspects of the cockpit configuration of the multirole combat aircraft - Vlačić, Slaviša I.; Knežević, Aleksandar Z.; Pekić, Nikola Đ. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Multirole combat aircraft represent a dominant category of combat planes. They can perform many different assigned taskssuch as those of- primary fighters, bombers and reconnaissance aircraft. In the execution of some tasks, it is evident that the crew of multirole combat aircraft is overloaded.This fact imposes the use of the two-seat cockpit configuration instead of the most common single seat cockpit configuration. Both configurations have their advantages and disadvantages, which requires a careful consideration of some tehnical and tactical aspects in the cockpit configuration of the multirole combat aircraft fleet. Some of the most important apects are considered in this paper. Introduction Multirole combat aircraft belong to a tactical combat aircraft category intended for the execution of many different tasks such as those of bombers, fighters, attack andreconnaissance aircraft. They were developed from fighter aircraft and emerged as a result of a fast technological advance at the domain of electronic equipment and weapon systems. Widening the combat capabilities of multirole aircraft in comparison to fighter aircraft from which they emerged imposes the reassessment of the attitudes towards the cockpit configuration, i.e. towards the decision which configuration to implement – one or two seat variant. Historical approach to cockpit configuration From the historical point of view, fighter planes, predecessors of multirole combat aircraft, developed in two directions: day fighters and fighters designated for accomplishing tasks in Instrumental Meteorological Conditions and by night. Fighter planes from the first category were mostly single seaters and the second ones were two seaters. In a two seater, the rear cockpit was usually occupied by qualified radar/weapon officers and rarely by qualified pilots. The complexity of fighter planes imposed a need for designing two seaters for pilot training. The ratio between two and single seaters in the 2nd and 3rd generation of combat planes was similar for the western and eastern models. The share of two seaters was between 13 and 18 percent. The fast development of electronic equipment and precisely guided ammunition has led to a significant evolution of existing fighters. Through the programs of comprehensive modernization they have become true multirole combat aircraft. This category was accepted by small airforces as well as by large ones. Correlation between technical-technological advance and crew overloading A wide spectrum of tasks performed by multirole combat aircraft was achieved by advance in the domain of navigational, radar and sensor systems as well as in information and communication technologies. All the mentioned systems and subsystems enabled a higher level of situation awareness of the pilot and his better task completion, but his overloading significantly increased. Therefore, decreasing crew task overloading has become a significant aspect in formulating requests for the cockpit layout. Solving the problem of crew overloading during the past two decades has taken two directions. The first was keeping the single seat cockpit configuration and the second one was the customization of two seat trainers for multirole combat tasks. In order to explain these two directions, the following 4th generation airplanes in different variants were considered: Eurofighter, F-15, F-16, F/A-18, JAS-39 Gripen, MiG-29, Su-27/30 and Rafale. The first direction includes airplanes such as Eurofighter and JAS-39 Gripen whilst the second, to a greater or lesser extent, includes F-15, F-16, F/A-18, MiG-29, Su-27/30 and Rafale. Technical factors of configuring multirole combat aircraft cockpit configuration Single seaters were preferred by the countries that in their initial tactical requirements required solely the fighter airplane. With changing circumstances, these countries redesigned their projects and upgraded them to multirole platforms. A smaller number of two seaters were justified by their higher acquisition price (10% higher) and by higher direct operational costs during the life cycle. Pilot overloading was reduced by the application of highly automatized systems, digital flight control systems and carefree handling, GPWS, and helmet-mounted cueing systems. A typical example is Eurofighter. Preferences for the two-seat cockpit layout over single seaters is evident in the case of Rafale and also in the case of F-15, F-16, F/A-18 and Su-27/30 - especially in the case of planes built after 2000. From the very beginning, Rafale was developed as a multirole platform. The other considered airplanes were developed as single seaters. However, after some combat and exploitation experience, the two-seat cockpit configuration is preferred nowadays. The share of two seaters in the total number of multirole combat airplanes is experiencing growth. In certain cases, as in the example of MiG-29M/M2, single seat layouts are produced out of two-seat cockpit airplanes. Multirole characteristics and the growth of combat capabilities of the two-seat configuration resulted in supplying the rear cockpit with equipment and devices alongside with enlarged authorization on decision process and actions against airborne and ground targets. Enhanced coordination between crew members due to the application of these technological solutions is also noticeable. Technical factors of configuring multirole combat aircraft cockpit configuration Two-seat models of multirole combat airplanes have higher MDZFW (Maximum Design Zero Fuel Weight) and less internal fuel weight. The consequence is a smaller tactical range. In order to extend the tactical range of two seaters, Conformal Fuel Tanks (CFT) are applied. As an effect, the CFT increase aerodynamic drag, reduce G overload and reduce maximum speed as well as aircraft acceleration. This category of fuel tanks is impossible to jettison, and that is why this configuration is used as a forced solution. A typical example is F-16 and its latest block versions dedicated to fighter-bomber tasks. No matter what the tasks of the multirole combat aircraft are, if there is a second crew member in the rear cockpit, his training is necessary. In certain airforces the pilot in the rear cockpit is preferred, whilst others have weapon systems officers. The concept of two-crew member functioning was devised through the independent and autonomous use of sensors data and individual detecting and acting upon targets from both cockpits. The operator in the rear cockpit wears a helmet-mounted cueing system which additionally increases the efficiency of the aircraft as a platform. Conclusion Rapid development of electronic equipment and precisely guided ammunition has allowed the evolution of fighters into multirole combat airplanes. Technical and technological advance was perceived through the installation of multifunctional radars capable of working in numerous modes, optical sensors, equipment for self-protection and electronic countermeasures as well as data-link devices. These technical subsystems have provided to the pilot a means for a higher level of situational awareness and more high quality, effective and safer task completion. With no doubt, this process increased pilot task burden and raised a question of configuring combat aircraft cockpits as single seaters or two seaters. It is also obvious that single seat planes are cheaper in exploatation than two seaters. In order to reduce crew overloading and increase combat plane efficiency, a high level of automatization was applied, based on digital flight controls careless airplane handling, a GPWS (ground proximity warning system) and a helmet-mounted cueing system. The fusion of sensor data was also enabled. The exploitation experience and lessons learned from local conflicts had a significant impact upon the increase of the number of two-seat multirole combat airplanes. It is evident that the two-seat cockpit configuration prevails in today’s production of multirole combat aircraft, or at least has a higher share in the serial production than it was the case in the first production lots. Configuring a fleet of multirole combat aircraft with two seaters is more evident in the case of smaller airforces that are in need of a true multirole platform because of the unification of their aircraft fleets. Though it stands that a smaller tactical range and a possibility of loss of two crew members are two-seater disadvantages, the number of acquired two seaters is still far from desired, especially in cases when there is a need for fighter-bomber and interdiction strike tasks. On the basis of available statistics, it can be concluded that the number of two-seated cockpit airplanes have experienced growth in the past two decades and that they are preferred by airforces with extensive combat experience as well as by airforce experts out of the circles of aircraft manufacturers and armament dealers.